Enhancement of Cement Sand Brick Incorporating Spent Catalyst and Copper Slag as Sustainable Partial Sand Replacements - Mohd Azwan Abdullah, Alfian Noor Firdaus; A. MAJID, MASNI; KAMARUDDIN, KHAIROL; Wajil, Redzkhan; Nur Khairunnisa Abdullah (International Journal of Integrated Engineering, 2025)
The use of waste materials in the manufacturing of cement sand brick constitutes a big step forward in sustainable building approaches. The partial sand replacement with waste materials, especially residual materials that can be reused in the field of construction such as spent catalyst and copper slag, has the potential to minimize environmental pollution and lead to more sustainable buildings. This study used spent catalyst and copper slag as a partial sand replacement material ranging 10% to 90% and examines the effect on the properties of cement sand bricks. Apart from that, the study used the Design Expert software approach to systematically analyzed the effect of various materials on the compressive strength and hardened density of cement sand brick. It was used to optimize the mix proportions and analyzed the correlations between four factors variables: targeted density, cement to sand ratio, proportion of sand and spent catalyst to copper slag ratio and the two responses: compressive strength and hardened density. The results show that spent catalyst and copper slag has greatly increases the compressive strength of the brick up to 26.98 MPa while hardened density reached the highest 2009.09kg/ . Hence, the replacement of 10% spent catalyst has greatly enhance the compressive strength of cement sand brick while 90% replacement of copper slag has increased the hardened density.